1 - Ebola Crisis in West Africa as the Embodiment of the World. Arguing for a Non-conventional Epistemology of Disease Aetiology - Jacquineau Azétsop,; Ludovic Lado,; Armel Setubi Fosso, (African Sociological Review, 2020)
The recent Ebola crisis in the Mano River countries in West Africa is not only a public health problem but a social problem which results from historical processes and socioeconomic arrangements that have subtly crippled people’s agency, destroyed social cohesion and reduced opportunities for human flourishing. The embodiment of social ills as disease challenges biased-popular accounts which erase the link that exists between the spread of the virus and social structures. The national, regional and transnational tales of the Ebola epidemic cannot be undermined, because the human body disclosed the homicidal logic of social entities that have been entertaining the civilization of subtle violence in these postcolonial countries where populations are confronted with misery.